PENGARUH FASILITAS DAN KUALITAS LAYANAN TERHADAP KEPUASAN WISATAWAN PADA OBJEK WISATA KAMPUNG BATU MALAKASARI - Abdullah, Husni; Herlinawati, Erna; Sumawidjaja, Riyandi Nur (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the influence of facilities and service quality on tourist satisfaction at the Kampung Batu Malakasari tourist attraction. Using a quantitative method grounded in positivist philosophy, the study collected data by distributing questionnaires to 100 visitors of Kampung Batu Malakasari through a simple random sampling technique. The analytical method employed was multiple linear regression analysis. The results of the study indicate that, partially, facilities have a significant and positive effect on tourist satisfaction, and service quality also has a significant and positive effect on tourist satisfaction. Simultaneously, facilities and service quality significantly influence tourist satisfaction. The better the tourists' perceptions of the facilities and service quality, the higher their satisfaction due to the reduced gap between expectations and service performance. Consumer satisfaction reflects the fulfillment of consumer expectations, which is closely linked to how the company strives to meet those expectations, influenced by the facilities and service quality offered. Keywords: